Surprising Efficiency Enhancement of Cu2ZnSn(S, Se)4 Solar Cells with Abnormal Zn/Sn Ratios. Issue 11 (13th September 2020) - Ge, Sijie; Xu, Han; Huang, Yuxiang; Karunakaran, Santhosh Kumar; Hong, Ruijiang; Li, Jianjun; Mai, Yaohua; Gu, Ening; Lin, Xianzhong; Yang, Guowei
Abstract : The elemental proportion of Cu poor and Zn rich in Cu2 ZnSn(S, Se)4 (CZTSSe) is well established for achieving highly efficient CZTSSe solar cells. However, how high Zn/Sn ratio can the complicated CZTSSe thin film tolerate remains a question. Therefore, herein, the well control of Zn/Sn ratio in CZTSSe thin film is obtained by multi‐spin‐coating and tuning the initial Zn/Sn ratio in the Cu–Zn–Sn–S precursor ink from 1.0 to 1.9. It is found that the Zn/Sn on the surface of CZTSSe absorber can self‐regulate to around 1.2 even with Zn/Sn ratio up to 1.9 in the precursor solution. Excess Zn presented as Zn(S, Se) secondary phase not only concentrate near the bottom area, but also widely distribute at the grain boundaries (GBs). In addition, it is found that the Zn(S, Se) secondary phase at GBs can promote current transport as revealed by conductive atomic force microscopy measurement. The surface roughness and grain size of the resulting CZTSSe absorber increased, whereas the MoSe2 thickness was reduced with increasing Zn/Sn ratio. More importantly, the device performance increased from 4.5% to 10.0% with a significant decrease in V OC deficit from 0.73 to 0.58 V when the Zn/Sn ratio increases from 1.0 to 1.5 in the precursor ink. Abstract : The increase of Zn content in Cu2 ZnSn(S, Se)4 films helps the grain growth and reduction of MoSe2 thickness. The excessive Zn segregated to grain boundaries could passivate the defects. Accordingly, the conversion efficiencies of resulting CZTSSe solar cells increase significantly from 4.5% to 10.0% when Zn/Sn ratio rises from 1.0 to 1.5.